Pragmatic Functions of Humor in Indonesian Podcasts: Implications for Intercultural Competence in Language Learning - Sari, Lusi Komala; Melan, Melan; Onwuagboke, Bede Blaise Chukwunyere (Actual Insight, 2025)
This study explores the strategic functions of humor in an Indonesian podcast conversation between Raditya Dika and Pras Teguh. While humor in digital media is widely discussed, its pragmatic and cultural dimensions in Southeast Asian podcast discourse remain underexamined. Using a pragmatic linguistic framework and cultural discourse analysis, this study reveals that humor fulfills three key functions: building social rapport, mitigating face-threatening acts, and maintaining discourse coherence. The analysis draws on five major theories: incongruity, superiority, relief, general theory of verbal humor, and multimodal strategies. Methodologically, the study integrates verbal and non-verbal cues in naturalistic podcast data to capture how humor operates in spontaneous, informal interactions. The findings also show that intertextual references, cultural expressions, and soft stereotypes embedded in jokes reflect Indonesia’s high-context communication style and function as identity negotiation tools in the digital public sphere. This research contributes a Southeast Asian perspective to digital humor studies and highlights humor’s pedagogical value. It suggests that podcast-based humor, when contextually analyzed, can support language instruction by enhancing learners’ pragmatic awareness, intercultural sensitivity, and communicative competence.